Exploring the word formation process on Rich Brian’s official music video comments - Syifa Dwi Mutiah; Didin Nuruddin Hidayat; Alek Alek (Universitas Islam Sultan Agung, 2021)
This study attempted to explore the process of word formation and its social function of slang words on Rich Brian's official music video, precisely in the comment section of the newest song of him, D.O.A that released on 25 August 2020. This study employed discourse and sociolinguistics aspects; hence, this study's research design was a descriptive qualitative. Additionally, this study's object was a one-month comment section of Rich Brian's newest song official music video. Furthermore, there were two sources of data, primary and secondary data sources. The primary data were a comment section of Rich Brian's newest official song music video, while the secondary source was from available works of literature and urban dictionary. Therefore, to collect the data, this study did the documentation from the D.O.A. official music video from one-month duration comments. As the data obtained, there were 49 slang words found. Then, they were analyzed through Yule (2010)’s theory as the basis of word formation process standard, while Zhou & Fan (2013)’s theory was used as the basis of word formation function standard. Data analysis is divided into several steps: reading, collecting, classifying, and analyzing the data. The result showed that derivation was the highest frequency of the word-formation process. It was 22%, the acronym was 18%, coinage was 16%, the conversion was 14%, blending was 12%, compounding was 8%, clipping was 6%, borrowing and multiple processes were 2% of each. Besides, the highest social function was to express emotive feeling with 49 % quantity of the frequency. The second higher was to pursue self-identity, achieving politeness was 8%. This study suggested a more in-depth analysis of non-standard languages, such as swear words or taboo words and emoticon that can be done through a social semiotic approach.